Determination of ghrelin immunoreactivity in the rat stomach after fasting and refeeding - Sonmez, Mehmet Fatih; Ozan, Enver (Elsevier Gmbh, Urban & Fischer Verlag, 2007)
Ghrelin is a recently discovered hormone secreted by cells of the stomach. The aim of this study was to investigate fasting and refeeding induced alterations on ghrelin immunolabelling of cells of the stomach. Thirty-six adult mate Wistar rats were used in this study. Rats were divided into six groups. Group I: control group; Group II: rats fasted for 7 days; Group III: rats fed for 1 day after 7 days of fasting; Group IV: rats fed for 3 days after 7 days of fasting; Group V: rats fed for 5 days after 7 days of fasting; Group VI: rats fed for 7 days after 7 days of fasting. At the end of the experiment, rats were sacrificed and stomach tissues were processed for imunohistochemistry to localize ghrelin. Ghrelin-immunopositive cells were detected only in the mucosal lining of the stomach. After fasting for 7 days, the number of ghrelin-immunopositive cells increased significantly compared to the control rats. Following refeeding, the number of ghrelin-immunoreactive cells was reduced to a level comparable to the controls. Therefore, fasting and refeeding after fasting were observed to result in changes in ghrelin immunoreactivity in the cells of the stomach. We conclude that ghrelin is highly expressed in the stomach and that fasting increases the expression of ghrelin in the stomach, but this expression decreases after refeeding. Our results indicate that regutation of ghrelin is a process probably involved in the long-term control of nutritional states. (c) 2007 Elsevier GmbH. All rights reserved.
4th Asian-Pacific-International-Congress of Anatomists (APICA 2005) -- SEP 07-10, 2005 -- Kusadasi, TURKEY
Keywords: stomach; ghretin; fasting; immunohistochemistry; rats